A Formal Typology of Reflexives1. (April 2017) - Déchaine, Rose‐Marie; Wiltschko, Martina
Abstract: Starting with the observation that reflexives do not form a homogenous class, we develop a formal typology for reflexives. In particular, on the basis of data from English (Germanic), French (Romance), Shona (Bantu), Plains Cree (Algonquian), and Halkomelem (Salish), we argue for the existence of (at least) five categorically distinct reflexive forms: D‐reflexives, φ‐reflexives, Class‐reflexives, n ‐reflexives, and N‐reflexives. We present the following arguments in support of this typology: (i) reflexive forms differ in their syntactic distribution; (ii) reflexive forms differ in the syntactic parallelism they exhibit; (iii) reflexive forms differ in the patterns of multi‐functionality they exhibit; (iv) reflexive forms differ in their syntactic integration into the clause; (v) reflexive forms differ in their semantic mode of composition. The analysis that we develop is couched within the Interface Syntax model of Wiltschko & Déchaine (2010), according to which sound‐meaning bundles freely associate with a universally defined syntactic spine.